Anti-Corruption Education at Universitas Negeri Semarang: What Benefits Can Students Get? (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Corruption is the main problem faced by countries in the world. Corruption is considered an extraordinary crime; therefore, eradicating it also requires extraordinary action. Education is one way to reduce the potential for Corruption. This paper will discuss implementing anti-corruption education courses at the Universitas Negeri Semarang and the benefits of the Anti-Corruption Education (PAK) course for students. To achieve it, the research methods applied are quantitative and qualitative. Quantitative data were analyzed using descriptive statistics. While qualitative data were analyzed using qualitative analysis. The results showed that implementing anti-corruption education courses, starting from lesson planning, implementation to learning evaluation, had gone well. Students taking part in the lectures feel that there are benefits, including increased knowledge of anti-corruption and a commitment not to corrupt in either life inside the campus or outside the campus.